THE EFFECTIVENESS OF APPLYING ESA METHOD TOWARDS STUDENTS’ ENGLISH VOCABULARY MASTERY - Vikasari, Rully May (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2019)
Inspired by difficulties of grade 8 students of SMPN 4 Praya, Central Lombok in increasing their vocabulary mastery, the current study applied ESA (Engage Study Active) method to overcome the situation. The fundamental contribution of vocabulary in learning a foreign language encouraged the researcher to find a way to improve students’ vocabulary mastery. In an attempt to find the solution, the study was designed as a quasi-experimental study at SMPN (public junior high school) 4 Praya. To conduct the study, the researcher had conducted a preliminary study to collect information from the class to identify problems occurred in the school during vocabulary learning. By applying mixed method, this study was aimed to find the effectiveness of ESA method using the quantitative method and to see the improvement on the students’ mastery qualitatively by conducting classroom observation to see the quality of interaction in the class using English as the target language. Throughout the study, quantitative data showed increase in students’ vocabulary mastery after being treated using ESA method, in which the mean score of the pre-test of 53 increased in the post-test of 75. The result was found using descriptive statistic analysis towards students’ pretest and posttest results. Qualitatively, the observers’ notes also indicated increase in terms of students’ vocabulary mastery by viewing students’ engagements during classroom interactions. It can be concluded that ESA method may increase students’ English vocabulary mastery in writing class.